POTENTIAL OF PIPER CHABA FOR THE MANAGEMENT OF THE STORED-PRODUCT PEST (CALLOSOBRUCHUS CHINENSIS): POTENTIAL OF PIPER CHABA FOR THE MANAGEMENT OF THE STORED-PRODUCT PEST - ABHISHEK MUKHERJEE; ROHAN DAS; DEBOJOTI CHAKRABORTY (The Journal of Research ANGRAU, 2026)
The present study investigated the insect-repellent potential of Piper chaba (Piperaceae)stem in multiple formulations-dry powder, fume and water extract-against the pulse beetleCallosobruchus chinensis (Coleoptera: Bruchidae), a major pest of stored grains. With theincreasing concern over pesticide resistance, toxicity to non-target organisms and residue hazardsassociated with synthetic insecticides, this research emphasises plant-based alternatives forsustainable pest management. Bioassays were conducted in I-tube (wind tunnel) to evaluaterepellency using various concentrations of each formulation, and the results were statisticallyanalysed using chi-square tests and regression analysis. The dry powder of P. chabastem showeda clear dose-dependent repellent response, with 1.75 g dry powder yielding 96.66% repellency( ² = 29.36, p < 0.001). Similarly, the fume exhibited full repellency at higher release rates (2–4ml/min) compared to 60% at 0.5 ml/min ( ² = 88.71, p < 0.001). Water extracts followed the sametrend, with 100% extract achieving complete repellency and diluted forms showing reducedeffectiveness ( ² = 66.25, p < 0.001). Phytochemical screening confirmed the presence ofalkaloids, flavonoids, terpenoids, and phenols compounds previously associated with insecticidalactivity. Infrared spectroscopy (IR) further validated the presence of functional groups such asO–H, C–H, and C=O, indicative of bioactive molecules. The findings establish P. chaba as apotent natural repellent with formulation-specific and concentration-dependent efficacy. Notably,the fume exhibits the highest repellency and richest phytochemical profile. This highlights P.chaba’s promise in eco-friendly pest control strategies, although further research is needed toassess toxicity on non-target species, residue safety, and field-level applicability.